A disseminação das políticas públicas locais de economia solidária no Brasil: os casos de São Paulo e Osasco - Bitelman, Marina Farkas (2008)
The present work aims at comprehending how public policies of Solidarity Economy in the Brasilian subnational context have been disseminated since the time when they begun, in the 1990s. The recent growth in the number of municipality and state governments which have implemented public policies of Solidarity Economy has not yet been followed by researches on the dissemination process of these governmental initiatives. This work intends to contribute to overcome this gap in literature about local public policies analyzing the dissemination of local public policies of Solidarity Economy in Brasil, drowing attention to the important role of social actors. The research was held by means of two specific case studies, the first one of the city of São Paulo during Marta Suplicy’s mayorship, and the other of the city of Osasco, under Emídio de Souza’s mayorship.